Distinguishing between void models and dark energy with cosmic parallax and redshift drift - Quartin, Miguel; Amendola, Luca (Arxiv, 2009)
Two recently proposed techniques, involving the measurement of the cosmic parallax and redshift drift, provide novel ways of directing probing (over a time-span of several years) the background metric of the universe and therefore shed light on the dark energy conundrum. The former makes use of upcoming high-precision astrometry measurements to either observe or put tight constraints on cosmological anisotropy for off-center observers, while the latter employs high-precision spectroscopy to give an independent test of the present acceleration of the universe. In this paper, we show that both methods can break the degeneracy between LTB void models and more traditional dark energy theories. Using the near-future observational missions Gaia and CODEX we show that this distinction might be made with high confidence levels in the course of a decade.